HIKAYAT NABI LOT: SEBUAH KAJIAN INTERTEKSTUAL DAN KAITANNYA DENGAN FENOMENA LGBT DI INDONESIA [The Saga of Prophet Lot: An Intertextual Study and Correlations to LGBT Phenomenon in Indonesia] - Siti Aisyah Hasanudin; Asep Yudha Wirajaya (TOTOBUANG, 2020)
This article aims to describe the correlations among intertextuality, hypogram, and transformation in the existing Saga of the Prophet Lot (hereinafter abbreviated as HNL) with the Story of the Prophet Lot (hereinafter abbreviated KNL) in the Holy Quran and also its correlations to the LGBT phenomenon in Indonesia.The problems in this article, that is (1) What is the intertextual relationship between HNL and KNL in the Holy Quran?, (2) How are the similarities and differences of HNL and KNL in the Holy Quran?, (3) What are the background creation of HNL? This article wants to prove that the ancient manuscript entitled HNL is a hypogram and transformation of the KNL contained in the Holy Quran.The method used in this article is content analysis because the authors intend to interpret the events contained in the HNL and then trace the Intertekstualnya relationship with the KNL found in the Holy Quran.In this article the similarities and differences in the two objects that will be examined are explained properly.This HNL script has similarities with KNL in the Holy Quran such as Prophet Lot was instructed by Allah SWT to preach his people such as about leaving their indecent behaviors; the arrival of the Angels at Prophet Lot’s home, Prophet Lot was expelled by his people, and punishment for the Sodomites. The differences only lie in the beginning of the story and at the end of the story of Prophet Lot.  Artikel ini bertujuan memaparkan hubungan intertekstual, hipogram, dan transformasi pada naskah Hikayat Nabi Lot (yang selanjutnya disingkat HNL) dengan Kisah Nabi Lot (yang selanjutnya disingkat KNL) dalam Alquran dan juga kaitannya dengan fenomena LGBT di Indonesia. Permasalahan dalam artikel ini, yaitu (1) Bagaimana hubungan intertekstual antara HNL dengan KNL dalam Alquran?, (2) Bagaimana persamaan dan perbedaan HNL dan KNL dalam Alquran?, (3) Apa yang menjadi latar belakang penciptaan HNL? Artikel ini membuktikan bahwa naskah kuno yang berjudul HNL merupakan hipogram dan transformasi dari KNL yang terdapat dalam Alquran. Metode yang digunakan dalam artikel ini adalah analisis konten karena penulis bermaksud menafsirkan peristiwa yang terdapat dalam HNL dan kemudian menelusuri hubungan intertekstualnya dengan KNL yang terdapat dalam Alquran. Artikel ini menjelaskan tentang persamaan dan perbedaan pada kedua objek yang akan di kaji. Naskah HNL memiliki persamaan dengan KNL dalam Alquran. Nabi Lot diperintahkan Allah SWT untuk berdakwah kepada kaumnya agar mau meninggalkan perilaku menyimpang, kedatangan para Malaikat ke rumah Nabi Lot, Nabi Lot diusir oleh kaumnya, dan hukuman bagi kaum Sodom. Adapun perbedaannya hanya terletak pada awal kisah dan akhir cerita Nabi Lot as. <w:LsdException Locked="false" Priority="